TINJAUAN LITERATUR: FENOMENA FANATISME SUPORTER DALAM PERSPEKTIF SOSIOLOGI OLAHRAGA - Cristian H. Siahaan, Stepanus; Noumora Panjaitan, Angel; Nurkadri; Apulita Br Kaban, Tiara; Murniati; Hendri Carlos Sitorus, Ferry; Haganta Ginting, Rendy (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aims to examine the phenomenon of supporter fanaticism from the perspective of sports sociology using a literature review method. Supporter fanaticism is a social phenomenon that has rapidly developed in modern sports and has a significant influence on social dynamics in society. This study analyzes various literature sources, including scientific journals, books, and academic articles related to supporter behavior, group solidarity, social identity, as well as the positive and negative impacts of sports fanaticism. The results of the study indicate that supporter fanaticism is not only a form of support for teams or athletes but also reflects social identity, solidarity, and group loyalty. However, excessive fanaticism can trigger social conflicts, aggressive behavior, and even violence among supporters.